Wykorzystanie sprzętu geodezyjnego w działaniach ratowniczych Państwowej Straży Pożarnej = The application of surveying equipment in the rescue operations of State Fire Service - Derezińska, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article describes the use of surveying equipment in the rescue work of the State Fire Service. The role of geodesy is becoming increasingly important in their operations, which is why they are more and more interested in the application of surveying techniques discussed below in the context of the various types of events. The use of a theodolite, a total station and a scanstation is shown during real accidents as well as during exercises and measurements taken in the simulated events.
Keywords: ratownictwo; sprzęt geodezyjny; geodezja w ratownictwie technicznym; tachimetr; Państwowa Straż Pożarna; rescue; surveying equipment; geodesy in technical rescue; total station; State Fire Service